The Student Teaching Equity Project: Exploring Teacher Candidates' Knowledge, Skills, and Beliefs. (January 2022) - Bell, Nicholas; Soslau, Elizabeth; Wilson, Chanelle
A quasi-experimental mixed-methods study was conducted to evaluate the effectiveness of an equity intervention on teacher candidates' abilities to articulate equity-based beliefs, and demonstrate and apply equity-based skills and knowledge. Three pre/post instruments were utilized. Treatment participants ( N = 35) were exposed to curricular modifications made to the traditional curriculum, including a workshop, panel event, online learning modules, and reflective postconferences. Quantitative findings showed a statistically significant treatment effect for treatment participants compared with candidates in the control group ( N = 83). Qualitative analyses showed that treatment participants articulated more equity-based language when describing their beliefs and intentions for their future classroom communities. Implications for practice and research are provided.